SENSORY DESCRIPTION OF SAWI-NEANAS JELLY CANDY WITH SWEETENER (SUCROSE, KELULUT HONEY AND STEVIA) - Farahiyati, Lana; Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma (Fakultas Pertanian Universitas Tanjungpura, 2025)
Jelly candy is a transparent and clear candy made from a mixture of fruit juice with the addition of gel-forming ingredients. Jelly candy with the addition of mustard greens has advantages because it has complete nutritional content and as a natural coloring in jelly candy. In addition, pineapple juice is added. Pineapple has a low pectin content for gel formation in jelly candy. The purpose of this study was to obtain the best sweetener formulation (sucrose, stingless bee honey and stevia) on the physicochemical and sensory characteristics of mustard greens-pineapple jelly candy. This study used a Randomized Block Design (RBD) with one factor, namely the comparison of sweetener formulations and there were 6 levels of treatment f0 (100%: 0%: 0%), f1 (50%: 50%: 0%), f2 (50%: 37.5%: 12.5%), f3 (50%: 25%: 25%), f4 (50%: 12.5%: 37.5%) and f5 (50%: 0%: 50%) with 4 replications. The results showed that the best treatment based on sensory tests and physicochemical characteristics was treatment f2 (50%: 37.5%: 12.5%).